2014
DOI: 10.1021/es4045852
|View full text |Cite
|
Sign up to set email alerts
|

Selenium(IV) Uptake by Maghemite (γ-Fe2O3)

Abstract: The mechanism of selenium(IV) uptake by maghemite was investigated on both the macroscopic and the molecular level. Maghemite nanoparticles exhibited fast adsorption kinetics toward selenium(IV). Batch experiments showed a decreased sorption with increasing pH (3.5-11). Ionic strength variations (0.01 to 0.1 M NaCl) had no significant influence on selenium(IV) uptake. Electrophoretic mobility measurements revealed a significant shift toward lower values of the isoelectric point of maghemite upon selenium(IV) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 96 publications
9
56
2
Order By: Relevance
“…Arsenic removal is the most studied case of magnetic iron oxides application in water treatment. 158,159,160,161,162,163,164,165,166 A number of publications for the removal of As, Cr(VI), Cu 2+ , Se and Co 2+ suggest ferrite nanoparticles as a magnetically activated system for water treatment. 102 In these studies, the adsorption capacity was getting higher following the decrease in the dimensions of nanoparticles.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…Arsenic removal is the most studied case of magnetic iron oxides application in water treatment. 158,159,160,161,162,163,164,165,166 A number of publications for the removal of As, Cr(VI), Cu 2+ , Se and Co 2+ suggest ferrite nanoparticles as a magnetically activated system for water treatment. 102 In these studies, the adsorption capacity was getting higher following the decrease in the dimensions of nanoparticles.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…The maximal contamination level of selenium in water is 50 lg/L (*0.6 lM) as defined by the US Environmental Protection Agency (EPA). In addition, 79 Se is a radionuclide found in nuclear fuel wastes, and it is a major environmental concern [3]. Inorganic selenium exists mainly in SeO 3 2-(selenite or Se(IV)) and SeO 4 2-(selenite or Se(VI)).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 79 Se is a radionuclide found in nuclear fuel wastes, and it is a major environmental concern [3]. Inorganic selenium exists mainly in SeO 3 2-(selenite or Se(IV)) and SeO 4 2-(selenite or Se(VI)). H 2 SeO 3 is a weak acid with two pK a values (2.6 and 8.3), while H 2 SeO 4 is a quite strong acid with its two pK a 's around 1.8 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impregnation of magnetite nanomaterials onto carbonaceous supports offers several unique advantages. Studies related to the uptake of selenium species have been reported; iron oxides [13][14][15][16][17][18][19], composite materials [20][21][22], and a recent review [23] on the subject. The formation of metal oxides such as magnetite (Fe 3 O 4 ) nanoparticles on the surface of activated carbon (AC) or within its pores may contribute to the formation of a stable composite material.…”
Section: Introductionmentioning
confidence: 99%